Speech Recognition in the Radiology Department: A Systematic Review. Issue 2 (June 2015) - Hammana, Imane; Lepanto, Luigi; Poder, Thomas; Bellemare, Christian; Ly, My-Sandra
Objective: to conduct a systematic review of the literature describing the impact of speech recognition systems on report error rates and productivity in radiology departments. Methods: The search was conducted for relevant papers published from January 1992 to October 2013. Comparative studies reporting any of the following outcomes were selected: error rates, departmental productivity, and radiologist productivity. The retrieved studies were assessed for quality and risk of bias. Results: The literature search identified 85 potentially relevant publications, but, based on the inclusion and exclusion criteria, only 20 were included. Most studies were before and after assessments with no control group. There was a large amount of heterogeneity due to differences in the imaging modalities assessed and the outcomes measured. The percentage of reports containing at least one error varied from 4.8% to 89% for speech recognition, and from 2.1% to 22% for transcription. Departmental productivity was improved with decreases in report turnaround times varying from 35% to 99%. Most studies found a lengthening of radiologist dictation time. Conclusion: Overall gains in departmental productivity were high, but radiologist productivity, as measured by the time to produce a report, was diminished.